Broad-spectrum suppression of bacterial pneumonia by aminoglycoside-propagated Acinetobacter baumannii. - M Indriati Hood-Pishchany; Ly Pham; Christiaan D Wijers; William J Burns; Kelli L Boyd; Lauren D Palmer; Eric P Skaar; Michael J Noto (PLoS Pathogens)
Antimicrobial resistance is increasing in pathogenic bacteria. Yet, the effect of antibiotic exposure on resistant bacteria has been underexplored and may affect pathogenesis. Here we describe the discovery that propagation of the human pathogen Acinetobacter baumannii in an aminoglycoside antibiotic results in alterations to the bacterium that interact with lung innate immunity resulting in enhanced bacterial clearance. Co-inoculation of mice with A. baumannii grown in the presence and absence of the aminoglycoside, kanamycin, induces enhanced clearance of a non-kanamycin-propagated strain. This finding can be replicated when kanamycin-propagated A. baumannii is killed prior to co-inoculation of mice, indicating the enhanced bacterial clearance results from interactions with innate host defenses in the lung. Infection with kanamycin-propagated A. baumannii alters the kinetics of phagocyte recruitment to the lung and reduces pro- and anti-inflammatory cytokine and chemokine production in the lung and blood. This culminates in reduced histopathologic evidence of lung injury during infection despite enhanced bacterial clearance. Further, the antibacterial response induced by killed aminoglycoside-propagated A. baumannii enhances the clearance of multiple clinically relevant Gram-negative pathogens from the lungs of infected mice. Together, these findings exemplify cooperation between antibiotics and the host immune system that affords protection against multiple antibiotic-resistant bacterial pathogens. Further, these findings highlight the potential for the development of a broad-spectrum therapeutic that exploits a similar mechanism to that described here and acts as an innate immunity modulator.